Brachial artery blood flow dynamics during sinusoidal leg cycling exercise in humans. Issue 19 (9th October 2017) - Fukuba, Yoshiyuki; Endo, Masako Y; Kondo, Ayaka; Kikugawa, Yuka; Miura, Kohei; Kashima, Hideaki; Fujimoto, Masaki; Hayashi, Naoyuki; Fukuoka, Yoshiyuki; Koga, Shunsaku
Abstract: To explore the control of the peripheral circulation of a nonworking upper limb during leg cycling exercise, blood flow (BF) dynamics in the brachial artery (BA) were determined using a sinusoidal work rate (WR) exercise. Ten healthy subjects performed upright leg cycling exercise at a constant WR for 30 min, followed by 16 min of sinusoidal WR consisting of 4‐min periods of WR fluctuating between a minimum output of 20 W and a maximum output corresponding to ventilatory threshold (VT). Throughout the protocol, pulmonary gas exchange, heart rate (HR), mean arterial blood pressure (MAP), blood velocity (BV), and cross‐sectional area of the BA, forearm skin BF (SBF), and sweating rate (SR) were measured. Each variable was fitted to a sinusoidal model with phase shift ( θ ) and amplitude (A). Nearly all variables closely fit a sinusoidal model. Variables relating to oxygen transport, such as V O2 and HR, followed the sinusoidal WR pattern with certain delays ( θ : V O2 ; 51.4 ± 4.0°, HR; 41.8 ± 5.4°, mean ± SD). Conversely, BF response in the BA was approximately in antiphase (175.1 ± 28.9°) with a relatively large A, whereas the phase of forearm SBF was dissimilar (65.8 ± 35.9°). Thus, the change of BF through a conduit artery to the nonworking upper limb appears to be the reverse when WR fluctuates during sinusoidal leg exercise, and it appears unlikely that this could be ascribed exclusively to altering the downstream circulation to forearm skin. Abstract : This study quantified the circulatory dynamics of blood flow (BF) to an inactive upper limb during leg cycling exercise using a sinusoidal work rate forcing function. BF in the brachial artery showed a clear sinusoidal response, with 180° phase delay following work rate fluctuation. This was not compatible with that of forearm skin BF.